CURRENT SITUATION IN OUR ECONOMY OF TOTAL QUALITY MANAGEMENT - Božović, Neško (BizInfo Blace, 2012)
The theory has confirmed the view that the appropriate organizational culture enables success in implementation of Total Quality Management (TQM). Conducted research points on characteristics of organizational culture in the relevant sample of enterprises in Serbia. The factors of the organization that affect on shaping the organizational culture of the business system were separated by using analytical approach. This creates the basis for the designing model of necessary changes in the organizational culture that ensures successful implementation of TQM.